2019
DOI: 10.1073/pnas.1811380116
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of Vγ2Vδ2 T cells programs sustained effector memory responses that control tuberculosis in nonhuman primates

Abstract: Tuberculosis (TB) remains a leading killer among infectious diseases, and a better TB vaccine is urgently needed. The critical components and mechanisms of vaccine-induced protection againstMycobacterium tuberculosis(Mtb) remain incompletely defined. Our previous studies demonstrate that Vγ2Vδ2 T cells specific for (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMBPP) phosphoantigen are unique in primates as multifunctional effectors of immune protection against TB infection. Here, we selectively immunized V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 64 publications
0
77
0
Order By: Relevance
“…Only a single study has reported BAL cd T-cell numbers in healthy and HIV-infected participants where there was a significant increase in total cd cells during HIV infection, but the delta chain usage was not determined. 93 NHP studies will be critical in determining whether host-directed therapy targeting Vd2 T cells 94 95 These cells are suggested to participate in the control of CMV replication and display potent anti-CMV responses in vitro. Na€ ıve macaques are able to induce robust primary and recall Vd2 responses to BCG vaccination in the periphery and lung, while SIV-infected macaques showed no response to BCG in either site.…”
Section: Impact On Coinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a single study has reported BAL cd T-cell numbers in healthy and HIV-infected participants where there was a significant increase in total cd cells during HIV infection, but the delta chain usage was not determined. 93 NHP studies will be critical in determining whether host-directed therapy targeting Vd2 T cells 94 95 These cells are suggested to participate in the control of CMV replication and display potent anti-CMV responses in vitro. Na€ ıve macaques are able to induce robust primary and recall Vd2 responses to BCG vaccination in the periphery and lung, while SIV-infected macaques showed no response to BCG in either site.…”
Section: Impact On Coinfectionmentioning
confidence: 99%
“…92 Encouragingly, administration of ART improved NHP Vd2 responses to BCG, possibly due to reconstitution of Mtb-specific CD4 + T cells. 93 NHP studies will be critical in determining whether host-directed therapy targeting Vd2 T cells 94 can enhance protection against TB reactivation in HIV-infected populations.…”
Section: Impact On Coinfectionmentioning
confidence: 99%
“…Thus, defining immune responses associated with establishing and maintaining human LTBI remains challenging. NHPs, e.g., macaques, recapitulate multiple aspects of human Mtb infection and disease progression and are attractive animal models for studying LTBI (16, 33-38). We recently showed that rhesus macaques with asymptomatic Mtb infection harbor viable Mtb bacteria in their lungs for up to nine months(20).…”
Section: Discussionmentioning
confidence: 99%
“…We combined our decade‐long nanotechnology and TB immunology expertise to innovate the macrophage‐targeted selenium nanomaterials for synergistic antimicrobial and bactericidal destruction of Mtb in host cells. Virtually, selenium nanomaterials can function as anticancer agents, inhibit E. coli , S .…”
Section: Methodsmentioning
confidence: 99%